Importance of competitive dynamics of strategic groups: Opportunities and challenges - Rosário, Albérico Travassos; Raimundo, Ricardo Gomes (Administrative sciences, 2024)
The competitive dynamics of strategic groups perform a major role in shaping the competitive background of industries. Strategic groups are sets of companies within an industry that follow related strategies or have comparable characteristics, such as product offerings, target markets, or geographic scale. Understanding these dynamics is central for firms to spot opportunities and cope with challenges effectively. This paper reviews the literature on the competitive dynamics of strategic groups. It analyses the theoretical underpinnings of competitive dynamics of strategic groups and discusses the central dimensions of the concept, underscoring the importance of competitive dynamics for strategic groups. Our aim is to sum up these perspectives while providing a clear and integrated overview through a systematic literature review. Such systematic literature review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. PRISMA is a framework with evidence-based data designed to help authors carry out a systematic literature review. This systematic literature review sought to consolidate knowledge on this topic. A discussion on the theme is carried out, an ensuing conclusion came up and, finally, avenues for further research are recommended.